2018
DOI: 10.1017/s0007114518001010
|View full text |Cite
|
Sign up to set email alerts
|

Marine n-3 PUFA, heart rate variability and ventricular arrhythmias in patients on chronic dialysis: a cross-sectional study

Abstract: Marine n-3 PUFA may improve autonomic dysfunction by an increase in heart rate variability (HRV) and may reduce the risk of malignant ventricular arrhythmias. Only a few smaller studies have examined such effects in patients on chronic dialysis, who often have autonomic dysfunction and a high risk of sudden cardiac death, which accounts for almost 30 % of all deaths. This cross-sectional study investigated the association between the plasma phospholipid content of n-3 PUFA and 24-h HRV or ventricular arrhythmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…The HRV is an effective method to evaluate cardiac autonomic nervous function and has an independent prognostic value in chronic hemodialysis patients with increased risks for all-cause and sudden death [ 32 ]. The decreased HRV indices in ESKD patients reflect the impairment of the autonomic nervous regulation on the cardiovascular system, and is an independent predictor of cardiac death [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HRV is an effective method to evaluate cardiac autonomic nervous function and has an independent prognostic value in chronic hemodialysis patients with increased risks for all-cause and sudden death [ 32 ]. The decreased HRV indices in ESKD patients reflect the impairment of the autonomic nervous regulation on the cardiovascular system, and is an independent predictor of cardiac death [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability (HRV) is a noninvasive measurement to evaluate autonomic dysfunction that reflects beat-to-beat variability in the heart rate. A decrease in the HRV has an independent predictive value for the occurrence of various CVDs, especially ventricular arrhythmias and sudden cardiac death [ 8–10 ]. Our previous study proved that HRV indices decreased significantly in CKD5 patients, especially in patients with severe SHPT, while PTX could improve the reduced HRV parameters [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Svensson et al [ 29 ] randomized 43 HD patients to 1.7 g marine n -3 PUFA or control for three months with no effect observed of n -3 PUFA on 24-h time-domain HRV. A recently published cross sectional study from our center also failed to show associations between plasma phospholipid content of marine n -3 PUFA and time- and frequency domain HRV in 135 dialysis patients [ 30 ]. The present study is the largest study investigating the effects of marine n -3 PUFA supplements on autonomic function in patients on chronic dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Svensson et al measured LC n -3 PUFA in serum phospholipids in 30 patients and found no correlations with 24 h HRV measurements at baseline [ 18 ]. Rantanen et al measured LC n -3 PUFA in plasma phospholipids in 135 patients and found no significant associations with 24 h time-domain or frequency-domain HRV [ 34 ].…”
Section: Discussionmentioning
confidence: 99%